1998
DOI: 10.2337/diacare.21.10.1632
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Epidemiology of IDDM in Hokkaido, Japan: The Childhood IDDM Hokkaido Registry

Abstract: This is the first population-based, long-term epidemiological study of childhood IDDM from Japan. We observed a significantly higher annual incidence (per 100,000/year) of IDDM in female subjects (1.81), older age-groups (2.25 for 8-14 years), subjects with no family history of diabetes (1.26), diabetes onset in the spring (2.20), and an increased trend over the 20 years. In addition, the heterogeneity of IDDM among Japanese children needs to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
2
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 23 publications
(26 reference statements)
3
37
2
2
Order By: Relevance
“…The increase in the incidence of type 1 diabetes from 1973 to 1992 is almost certainly due to environmental factors. Matsuura and co-workers suggested that the year 1985, which had a high incidence of diabetes in their study, coincided with the 10-year time lag from the lowest breastfeeding rate in Japan, as reported in epidemiological studies from Norway and Sweden [20]. In addition, there was an epidemic of Echo 7 in 1986 and of Coxsackie B3 in 1987, both of which could be linked to the higher incidence in that period [24].…”
Section: Childhood Type 1 Diabetesmentioning
confidence: 64%
See 1 more Smart Citation
“…The increase in the incidence of type 1 diabetes from 1973 to 1992 is almost certainly due to environmental factors. Matsuura and co-workers suggested that the year 1985, which had a high incidence of diabetes in their study, coincided with the 10-year time lag from the lowest breastfeeding rate in Japan, as reported in epidemiological studies from Norway and Sweden [20]. In addition, there was an epidemic of Echo 7 in 1986 and of Coxsackie B3 in 1987, both of which could be linked to the higher incidence in that period [24].…”
Section: Childhood Type 1 Diabetesmentioning
confidence: 64%
“…The population-based, long-term epidemiological study of childhood type 1 diabetes in Japan, conducted by the Childhood IDDM Hokkaido Registry Study Group [20], reported that the incidence rates of 'classic' type 1 diabetes under 15 years ranged from 0.98 to 2.53 cases per 100,000 persons per year, and that the annual trend obviously increased over the 20-year period between 1973 and 1992, with an overall annual increase of 5.9% [8] (Table 1). The incidence was greatest among children of 10-14 years of age at onset (Table 1), as in most populations studied worldwide [21].…”
Section: Childhood Type 1 Diabetesmentioning
confidence: 99%
“…Geographic regions with higher T1D incidence generally do not show a sex bias. However, in Japanese, Oceanic, and African-American populations with lower disease incidence, a higher T1D incidence has been observed in females (67)(68)(69). In addition to sex effects on FIGURE 8.…”
Section: Sexual Dimorphism In Autoimmune Diseasementioning
confidence: 99%
“…In contrast, the Japanese population has one of the lowest incidence rate of T1D in the world, at 1.6 cases/100,000 individuals per year, suggesting that the Japanese population may either lack an important susceptibility gene or have a unique T1D protective gene [36,37]. However, AITD is the most frequent autoimmune disease in the population, present in approximately 7-8% of the general population [38,39].…”
Section: Nomenclaturementioning
confidence: 95%